Digital Teaching Skills Models: analysis of the most relevant international and national proposals (Revista Electrónica Calidad en la Educación Superior, 2021)
The creation and use of models or standards in digital teaching skills has been going on for years, through different initiatives that seek to establish criteria or standards that allow a strategic implementation of the use of technology in the pedagogical field. Therefore, it is considered important to analyze what has been recently developed and has great potential for use to improve teaching practice at the national level so as to identify those elements that make up the existing digital skills models that are feasible to be considered on a proposal focused on the distance and online education model.
Keywords: Digital competences; teacher; competency models